Surgical pulmonary embolectomy - an underestimated treatment option - Dariusz Zieliński; Andrzej Biederman (Termedia Publishing House, 2022)
It gave us great pleasure and interest to read the commentary of Zembala et al. on the article by Pruszczyk and Konstantinidis published in Kardiologia Polska [1, 2]. As outlined in the commentary, surgical embolectomy can provide excellent early and long-term outcomes. According to ESC guidelines for patients with acute pulmonary embolism surgical embolectomy is recommended when other forms of treatment have failed or are not feasible. Patients with high or intermediate risk acute pulmonary embolism requiring urgent treatment are a very heterogeneous group. At present, the 3 existing alternative therapies - thrombolysis, catheter-based therapy, and surgical embolectomy - are difficult to compare. Perhaps a large registry will shed some more light on the results of these methods.